Intervenções de saneamento básico em áreas de vilas e favelas: um estudo comparativo de duas experiências na região metropolitana de Belo Horizonte - Uende Aparecida Figueiredo Gomes (2009)
The objective of this study was to evaluate the adequacy of sanitation interventions in areas of towns and slums. The issues that were included in this study were related with necessity to review the concept of appropriates technologies and thus promote social participation andnew proposals for intersectorial actions in the context of initiatives in basic sanitation in areas of towns and slums. It was also the object of the study the possibility of not joining the systems of distribution of water and sanitation due to the inability to bear the costs and demand for urban land regularization. To discuss them, there was a case study that comparesthe sceneries in Aglomerado da Serra and in Nova Contagem, areas of towns and slums belonging to the Metropolitan Region of Belo Horizonte, that have been suffering interventions in basic sanitation. The adopted methodology consist the collect of documental evidences through documental analysis, the observation and implementation of semistructured interviews with professionals in this area and local communities. The interviews were transcribed, and then, organized and analyzed using the strategy of Analysis of Content. The results suggest there is a consensus among the tecnicians about the necessity to adoptintersectorial practices and to foster social participation within the context of basic sanitation. However, was observed that the individual erformance and informal interaction are in evidence at practice of intersectoral actions; its needed a more incisive orientation using an institutional point of view. As for social participation, the predominant view is related withthe involvement of community in order to enhance the sustainability of stocks, while the promotion of their self-organization and self-determination are not recognized or prioritized. Analyzing the pricing adequacy, is questioned the action of social tariffs as a form of subsidybecause of problems with the criteria for inclusion of users as beneficiaries, but also in relation to the structure of prices charged by the company of sanitation and its impact on the income of the poorest. As the urban land regularization it was noted that there is not a clearunderstanding about the implications of the lack of ownership of land in access to services and basic sanitation or the sector's role to solve this problem. Under communities the most predominant, on all issues, is that the high level of absence doesnt have as consequences the exclusion and restriction of access to goods and services, including those related to basic sanitation, but also reflects on the perpetuation and maintenance of these limitations, where people are included in cycles of poverty, and do not have the attention of society. It can be concluded that the structure of Brazilian society, with its high degree of misinformation and high rates of social inequality, is reflected in the concepts of interventions in sanitation, since makes the problems of slums and villages more complex, and in addition, hinders the understanding of reality to seek alternatives of action in order to transform it